Macroeconomic Determinates Of Stock Price for Industrial Companies Listed In Istanbul Stock Exchange - Hasa, Nawzad; Jalil Omer, Abdul; Othman, Bestoon; A Perot, Karwan; Abdulla Maji, Amer; Abdul kareem, Fria (International Journal of Psychosocial Rehabilitation, 2019)
This paper investigates the impact of changes in selected macroeconomic variables onthe BIST-KYDD Price Index in the Turkish stock market. The essential objective of the study is to examine the relation between the Industrial Index inthe Turkishh stock market and the macroeconomic factors. To determine macroeconomic factors influencing SPI. Detect the significant variables and their percent of influence on SPI. The study will examine the relationship between Turkish stock market activities by identifying variables thataffect,t particularly the Industrial Index of themarket,t by employing monthly data for the period January 2003 to December 2013. This study uses the computer software SPSS for applying the analysis. Ordinaryleasttsquaress regression is appliedton the series. Amultivariateeregressionnmodell computed onthe standardd OLSformulaa has been used to estimate the relationship. Based onthe regressionn coefficient, it was found thatinflationn,exchangee rate,moneyysupply,y andinterestt rate all hada negativee influence onthe BIST-KYDD index. The model was tested forautocorrelation,nhetroscedactism,y and multicollinearity and was approved to be clear. All the independent variables can explain 87.4% ofthe changee in the price ofthe BIST-KYDD index in Turkey. As an attempt to add to the growing body of empirical studies on the role of the macroeconomic environment and the stock market’s activity and to answer the question of whether or not the selected macroeconomic variables influence the stock market in the case of Turkey, this study will use developed econometric techniques to empirically investigate this question. Based on the results of thisstudy,y investors andpolicymakerss may see a reason to improve the financial system in an attempt to achieve higher levels of return andfewers risks.